Biofiltration of diluted landfill gas in an active loaded open-bed compost filter. (15th February 2020) - Fjelsted, L.; Scheutz, C.; Christensen, A.G.; Larsen, J.E.; Kjeldsen, P.
Highlights: A pilot-scale compost biofilter for treating diluted landfill gas at an old landfill. Preferential flows at the transition points between compost and the container wall. A methane oxidation rate of 460 g CH4 m −2 d −1 in an actively aerated biofilter. A tracer gas test showed good gas distribution at the bottom of the biofilter. Abstract: Microbial oxidation in a biofilter is a treatment solution for diluted landfill gas (LFG), for instance at old landfills, where LFG recovery is no longer feasible, or from remediation systems designed to cut off laterally migrating LFG. In this study, an actively loaded open-bed compost filter, designed for the treatment of diluted LFG, was tested at an old landfill in Denmark. An 18 m 3 biofilter was constructed in a 30 m 3 container loaded with LFG mixed with air, in order to obtain diluted LFG. The inlet concentration of methane (CH4 ) fluctuated between 4.4 and 9.2 vol% during the five tested flow campaigns, resulting in CH4 loads of 106–794 g CH4 m −2 d −1 . The maximum identified CH4 oxidation rate was 460 g m −2 d −1, with an overall CH4 oxidation efficiency of 58%. Due to preferential flows, especially along the edges of the filter at the transition points between the compost and the container wall, an overall CH4 oxidation efficiency of 100% was never achieved. However, pore gas profiles in selected areas in the filter material showed oxidation efficiencies close to 100%. The results were supported by tracer gas tests showing average oxidation efficiency in the nine measuring points of 89% at a CH4 load of 487 ± 64 g CH4 m −2 d −1 .